Adaptation to river bank erosion induced displacement in Koyra Upazila of Bangladesh - Md. Sadequr Rahman; Animesh Gain (Progress in Disaster Science, 2020)
River bank erosion negatively affects on people and their livelihood with their economic, social and psychological distress increasing over the time. Most of the people are vulnerable and their economic condition are fragile for internally displaced in Dakshin Bedkashi, Choramukha and Ghorilal villages of Koyra riverine area of Khulna district. Mixed research methods including quantitative and qualitative approach was applied by survey method, Key Informant Interview (KII), and Focus Group Discussion (FGD) to collect information.Most of the people do not exists sustainable livelihood framework (SLF) due to the acute poverty for river erosion. About 82.49% respondents' house were fully damaged and 26.27% respondents live besides the roads and embankments due to erosion. About 85.02% respondents were internally displaced/migrated or becoming homeless due to Kapothaksma and Shakbaria river erosion. About 76.27% respondents' occupational status were affected severely, 48.39% changed their livelihood and engaged with catching fish, 28.34% households suffer tremendous food crisis, 36.18% respondents' income is decreasing, 32.02% loss their land, and 91.94% respondents suffer psychological stress like anxiety, depression, dizziness, insomnia, unsteady gait, post traumatic stress disorder, somatoform etc. due to river erosion. About 94.24% and 34.10% respondents cope up, adjusted or adapted by reducing meals and extra workload. 75.58% respondents borrowed money from GO, NGOs, Mahajon, Co-operatives, and Relatives with high interest. 81.11% and 33.64% respondents adjusted or adapted by decreasing rate of school going children and adjusted through drop out their child from formal education due to river erosion. In this paper, it is observed as risk that river bank erosion is causal factors of migration, vulnerability and hindrances of rural socio-economic, cultural, psychological and environmental development. The people who affected by river bank erosion immediately migrate for safe shelter and later permanently for survival. Keywords: Adaptation, River bank erosion, Displacement, Vulnerability